Cover Image. (20th April 2018) - Mirzadeh, Elham; Akhbari, Kamran; White, Jonathan
Abstract : The cover image, by Elham Mirzadeh et al., is based on the Full Paper Mechanochemical conversion of nano potassium hydrogen terephthalate to thallium analogue nanoblocks with strong hydrogen bonding and straight chain metalophillic interactions, DOI:10.1002/aoc.4313 .